Validation of a therapeutic range for nitisinone in patients treated for tyrosinemia type 1 based on reduction of succinylacetone excretion. Issue 1 (14th March 2019) - Jack, Rhona M.; Scott, C. Ronald
Abstract: The drug nitisinone (NTBC; Orfadin, Vienna, Austria) has been used for the treatment of hereditary tyrosinemia type‐1 since 1991. Nitisinone effectively blocks the metabolism of tyrosine to prevent the formation of the toxic compound succinylacetone (and precursor fumarylacetoacetate) in affected children. Monitoring of plasma drug levels and urine succinylacetone can be used to assess compliance and adequate dose of drug. We present retrospective data from patient monitoring for over 10 years that provide validation of a target therapeutic range for nitisinone of 40 to 60 μmol/L. The target nitisinone range is justified as valid based on reduction of succinylacetone excretion. There was no statistical significance in succinylacetone excretion in mmol/mol creatinine above a level of 40 μmol/L plasma NTBC ( P > 0.05).